A compact microstrip feedline printed antenna with perturbed partial ground plane for UWB applications. Issue 9 (15th June 2021) - Kumar, Ranjeet; Sinha, Rashmi; Choubey, Arvind; Mahto, Santosh Kumar
Abstract: This article presents a simple compact microstrip feedline printed antenna that can minimize the consequences of frequency interference, thereby, providing good stable omnidirectional radiation pattern and transmission response within whole range of desired frequencies. The proposed antenna has two regular shaped hexagonal radiators, a mictrostrip‐fed line and a partially extended ground plane perturbed by a circular slot inserted at the centre. The partial ground plane with a circular slot at the center plays an important role in the broad band characteristics of the proposed antenna, because they can adjust the electromagnetic coupling effect between patch and ground plane and improve the impedance bandwidth. The simulation and measured results are in close agreement and show that a wide bandwidth of 10.39 GHz (2.52‐12.91 GHz) at −10 dBi return loss with voltage standing wave ratio less than two is achieved by this antenna. The antenna is compact (0.37λ × 0.24λ), has good radiation pattern, appreciable gain of 5.97 dBi and 134% fraction bandwidth which is favorable for ultra‐wide band applications such as S, C, X, WLAN, and WiMAX. The equivalent lumped circuit model of the proposed antenna is also presented for validation purpose. The proposed antenna in particular focusses on 3.4 to 3.6 GHz frequency band with centre frequency 3.5 GHz (sub 6 GHz 5G band) and WLAN/Wi‐Fi (3.6/4.9/5.9 GHz) applications.